CONSTITUINTES QUÍMICOS E ATIVIDADES BIOLÓGICAS DE Remijia DC. (RUBIACEAE): UMA REVISÃO - Fábio G. de Souza; Gabriel S. Crispim; Luana da C. Moreira; Cecilia V. Nunez (Química Nova)
Plants of Remijia DC. (Rubiaceae) are widely distributed in South America and are often known by the popular names of “quinas” and “quinas-falsas” because of their similarity to the genus Cinchona L. This study consisted of a review of the reported substances and biological activities found in the Remijia genus. For this purpose, information was collected from SciFinder, ScienceDirect, PubMed and Google Scholar databases by entering the term “Remijia”. It was found that only four species have been chemically and biologically studied: R. ferruginea, R. peruviana, R. pedunculata and R. purdieana. Thirty-eight substances of different chemical classes were found, such as: quinoline alkaloids, indole alkaloids, flavonoids, phenolic acids, steroids, and a triterpene. Among the substances produced by these plants, quinoline alkaloids stood out, with 12 substances identified. In addition, the extracts and isolated substances from this genus showed antioxidant, anti-inflammatory activity of TNF-α (tumor necrosis factor alpha) inhibition, antiplasmodial, wound healing, cytotoxic, anti-Trypanosoma, antifeedant, antimalarial, antihyperlipidemic, antihyperglycaemic and ferriprotoporphyrin IX inhibition activities. This review demonstrates the chemical variability found in Remijia species and encourages further chemical studies. The great preference observed by the Remijia species studied to date to produce quinoline and indole alkaloids indicates that they are the chemosystematic markers of the genus.